Kesan pembelajaran koperatif terhadap konsep kendiri akademik di dalam pendidikan perakaunan - Abdul Kadir, Suhaida; Lope Pihie, Zaidatol Akmaliah; Yaakub, Noran Fauziah; Elias, Habibah; Ahmad Tarmizi, Rohani (Universiti Putra Malaysia Press, 2004)
Academic self-concept is the individual's perception of his/her ability in academic field. Developing students with positive self-concept is important because high academic self-concept will help students to build confidence on high achievement. Researches abroad showed that cooperative learning is able to increase student self-concept. Right now, group learning strategy has been used in the Malaysian educational system. However, only a few empirical studies have been conducted to measure the effectiveness of the strategy in the Malaysian context. This paper reports the finding of an experimental study that was conducted at secondary schools. This study compared cooperative learning strategy with conventional strategy toward academic self-concept in accounting education. Students' perception of the implementation of cooperative learning strategy was obtained through structured open ended questions. The result of the study showed that academic self-concept of students in conventional learning groups was higher compared to cooperative learning groups. Nevertheless, qualitative data that were obtained explained in detail students' positive experiences. The implication of the study showed that cooperative learning strategy is suitable for implementation in Malaysia.